An Econometric Estimation of Impact of Economic Growth on Employment in Algeria during the Period (1994- 2018) - Sihem, Boudeb (Milev Journal of Research and Studies, 2020)
This paper aims at measuring the impact of economic growth on employment in Algeria during the period 1994- 2018. Using an Autoregressive Distributed Lag (ARdl) Model, the results show that the economic growth rates are insufficient to reduce unemployment rates